The directions of the Algerian administrative judge in ordering the threatening fine against the administration. - Khelafellah, Karima (Journal of Human Sciences, 2021)
Given that the administration rejoices the privileges of public authority, the issue subjecting it by astrainte in case of its refusal to execute the judicial decisions against it aroused considerable controversy in the ways of the administrative judge. Therefore, he was wavering and unstable, refraining from ordering it at first based on illogical grounds incompatible with the essence of law, at the same time .Nonetheless, with the Law 08/09, ( C C A P), the Administrative Judge obtained the astrainte power,  it has given more effectiveness to ensure the execution of administrative justice sentences issued against the administration. However, it is not mandatory for the administrative judge to pronounce it against the administration, it is up to his discretionary authority to reduce or cancel it, nor can we deny the negative impact of its frequent use by the administrative judge on the public treasury efficiency as it exposes its money to waste.